Prevalence and coexistence of locomotive syndrome with reduced mobility and metabolic syndrome: a cross-sectional study of 35,059 Japanese adults - Chihiro Goto; Kohei Maruya; Yasuhiro Morita; Tomoyuki Arai; Satoshi Yamaguchi; Keiko Yamada; Masaru Moriyama; Hideaki Ishibashi; Ryo Nakagawa (Scientific Reports)
Abstract Metabolic syndrome (MetS), marked by visceral obesity, hypertension, hyperglycemia, and dyslipidemia, elevates cardiovascular risk. Locomotive syndrome (LS), characterized by age-related mobility decline, often precedes frailty and sarcopenia. We investigated the prevalence and association between MetS and LS among Japanese middle-aged and older adults. This retrospective cross-sectional study was conducted using clinical records of 35,059 Japanese adults who underwent health check-ups between April 2021 and March 2022. MetS was diagnosed using the modified National Cholesterol Education Program Adult Treatment Panel III criteria, and LS was assessed using the LS risk test, which includes the stand-up test, two-step test, and the 25-question Geriatric Locomotive Function Scale. Among the participants, 2640 (7.5%) were diagnosed with MetS, and 5265 (15.0%) were classified as LS-positive. The prevalence of LS was significantly higher in individuals with MetS. The association between MetS and LS remained significant after adjusting for age and sex. We found that LS prevalence was higher in women than in men, though the primary association between MetS and LS remained consistent across both sexes. This large-scale real-world analysis emphasizes the need for integrating LS screening into routine check-ups to detect and manage MetS, aiding in the prevention of functional decline in aging populations.